THE INFLUENCE OF LIGHT INTENSITY ON RINUAK FISH (PSILOPSIS sp) BY SEROK (SCOOP NET) IN MANINJAU LAKE WEST SUMATERA - Kartika Rahma; Arthur Brown; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on 10 days in Maninjau Lake waters,West Sumatera Province. The purpose of research is to know the influence of light intensity on rinuak fishes. The method used in the research is the experimental fishing method. The research was conducted at night and the result that there is very noticeable to the influence of different light intensity to catches of rinuak fish.From three lamp power used (35,45 and 55 watt) it was proved the lamp with 45 watt power bring the lightest catches at much as 58 % of total catches,followed by 55 and 35 watts lamp power. The total catches is 98 kg. Fro annova test bring P value < 0,01 which mean the lamp power light bring significant effect on catches of rinuak.Keyword : Rinuak Fish, Light Intensity, 45 watt